Development of E-LKPD Based on Group Investigation Integrated with Citizen Science Project to Improve Analytical Thinking and Collaboration Abilities of Junior High School Students - Imam Sajidi; Parmin (Postgraduate, University of Mataram, 2025)
This study aims to develop and evaluate the effectiveness of an E-LKPD based on group investigation integrated with a citizen science project on ecology and biodiversity material for junior high school students. The research employed a 4D development model (Define, Design, Develop, Disseminate) and was conducted at SMP Negeri 13 Semarang with a sample of 32 Grade VII students selected via cluster random sampling. Data collection methods included interviews, observations, questionnaires, and tests. Validation by material and media experts yielded Aiken's V scores of 0.89 and 0.88, indicating high validity. The readability test scored 69.90% (very good), while the field practitioner test scored 98.07% (very feasible). The effectiveness analysis using N-Gain showed an increase in students' analytical thinking skills by 66.5% and collaboration skills by 62.30%, both categorized as moderate. These findings indicate that the E-LKPD is valid, practical, and moderately effective in enhancing students’ analytical thinking and collaboration skills in science learning.